Crédito para habitação no Brasil: histórico e desafios - Rodrigues, Luiza Betina Petroll (2009)
This work aims at analysing the evolution of brazilian housing finance in the light of existing literature and models adopted by other countries, to check the potential of housing credit growth in the next years. The main conclusions of this work are two. First, recent macroeconomic stability and important institutional change created a favourable scenario for housing credit growth, despite the fact that there are still important questions to be addressed specially juridical security. Secondly, even if these questions are solved and that housing credit becomes significantly cheaper than it is today, it will not be able to solve, alone, the problem of housing deficit. This problem requires extra effort in the form of subsidies, and, for extremely poor families, housing finance in the usual sense may not be the best answer